The Influence Of Convenience And Consumer Trust On Purchase Decisions On Shopee - Kurniawati, Dyah; Putri, Wahyu Prabawati; Laia, Erni Wati (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
This research aims to test and analyse the influence of convenience and consumer trust on purchasing decisions at Shopee. The sample used in this research was 100 respondents who had made purchases at Shopee using a purposive sampling technique. Data collection was carried out online, namely by using Google Forms. Data analysis techniques used multiple linear regression tests and hypothesis testing. The research results show that the variables of convenience and consumer trust have a positive and significant effect on purchasing decisions. The adjusted R Square value obtained is 0.874 or 87.4%. This means that the variables of convenience and consumer confidence in purchasing decisions have an influence of 87.4% and the remaining 12.6% is influenced by other variables not included in this study